Principal’s Strategy in Developing Human Resources of Islamic Educational Institutions - Hamid Hamid; Mohammad Afifulloh; Moh Muslim (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study examines the leadership strategies implemented by the principal of SMK Al Hasan Tengginah Proppo Pamekasan in developing the quality of human resources (HR) within the educational environment. Using a qualitative approach and an intrinsic case study design, data were collected through naturalistic observation, semi-structured interviews, and document analysis, and subsequently analyzed thematically. The findings show that the principal implements five integrated leadership strategies: moral guidance, capacity development, mentoring and collaboration, technological adaptation, and empowerment. These strategies significantly contribute to the enhancement of teachers’ professional competence, interpersonal skills, and motivation. The impact of this leadership practice extends to the improvement of educational quality, including learning models, teaching effectiveness, student learning motivation, and academic achievement. This study emphasizes that strategic leadership plays a central role in shaping a responsive, innovative, and sustainable educational environment. The integration between leadership theory and contextual implementation offers a comprehensive model for improving educational quality through systematic human resource development